Wood borer detection rates on wood packaging materials entering the United States during different phases of ISPM 15 implementation and regulatory changes - Haack, Robert A.; Hardin, Jesse A.; Caton, Barney P.; Petrice, Toby R. (Frontiers in Forests and Global Change, 2022)
Wood packaging material (WPM) used in international trade, such as crating and pallets, is recognized as a high-risk pathway for the introduction of bark- and wood-infesting insects (borers). The International Standards for Phytosanitary Measures No. 15 (ISPM 15), which sets treatment requirements for WPM, was adopted in 2002. The United States (US) implemented ISPM 15 during 2005-2006. We used 2003-2020 AQIM (Agriculture Quarantine Inspection Monitoring, conducted by USDA APHIS) data, based on standard random sampling, to compare pre-ISPM 15 borer detection in WPM entering the US (2003-2004) to detection rates during 2005-2006 (implementation phase), 2007-2009 (post-ISPM 15 when bark was not regulated) and 2010-2020 (post-ISPM 15 when bark was regulated). We examined borer detection rates overall for all AQIM WPM records and individually for the three main cargo survey programs within AQIM [Italian tiles, perishables, and general WPM (GWPM) for any WPM associated with containerized maritime imports], and individually for three major US trading partners (China, Italy, and Mexico). During 2003-2020, wood borers were detected in 180 of 87,571 consignments with WPM (0.21%). When compared to 2003-2004 (detection rate of 0.34%), detection rates fell 61% during 2005-2006, 47% during 2007-2009, and 36% during 2010-2020. Similar declines occurred for WPM associated with Italian tiles and perishables. However, for GWPM there was no significant reduction post-ISPM 15. WPM infestation rates were reduced significantly during various post-ISPM 15 periods for Italy and Mexico, but not for China. Seven families or subfamilies of borers were recorded in WPM with Cerambycidae and Scolytinae being most frequent. The incidence of WPM with bark fell significantly after the 2009 change to ISPM 15 that required debarked WPM. We discuss several factors that could influence the apparent effectiveness of ISPM 15.